Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

A quest for authenticity: Contemporary butch gender - Levitt, Heidi M.; Hiestand, Katherine R. (Sex Roles : A Journal of Research, 2004)
Un modèle d'identité butch contemporaine a été construit à partir de l'analyse d'une série d'entretiens semi-structurés avec des femmes identifiées comme butch qui ont décrit leur genre en relation avec leurs propres expériences et croyances. Le processus analytique impliquait une approche théorique fondée (Glaser & Strauss, 1967). Les résultats de l'étude décrivent comment les femmes identifiées comme butch conceptualisent leur identité de genre et comment cela affecte leurs relations sociales au sein des communautés lesbiennes et hétérosexuelles. La catégorie centrale de ce modèle (c.-à-d. Une quête d'authenticité) définit l'identité butch comme impliquant un processus continu de négociation entre un sens essentiel du genre lesbien et des exigences de présentation du genre qui sont comprises en relation avec la signification et la signification des genres à travers les contextes sociaux. . (Enregistrement de la base de données PsycINFO (c) 2019 APA, tous droits réservés)
Keywords: 2000 à aujourd'hui; 2000-2009; butch/femme; discipline; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; sciences humaines